Low-voltage operation mode of ASCENT-propelled pulsed plasma thruster - Lee Organski; Brian Jeffers; Patrick Gresham; Artur Kucharewicz; Alexey Shashurin (AIP Advances)
This study demonstrates the feasibility of operating a liquid-fed pulsed plasma thruster (PPT) at low voltages, in the magnetoplasmadynamic (MPD) arc range below 100 V, in contrast to conventional PPTs operating in the kV range. The system uses ASCENT (Advanced Spacecraft Energetic Nontoxic Propellant) as a propellant. Low voltage operation was achieved by eliminating long discharge electrodes and associated voltage drops. The designed thruster demonstrated consistent operation at discharge voltages of 50–150 V for discharge currents varying in the range of 2–8 kA. The measured V–I characteristics of the thruster’s discharge were consistent with self-field MPD arcs, and, correspondingly, the designed system can be classified as a pulsed-MPD thruster. We further confirmed the action of the accelerating Lorentz force on the propellant by measuring fast exhaust ion velocities in the range of 10–30 km/s. Photographic observations confirmed the formation of a plasma jet sourced from the ASCENT propellant, with minimal cathode spot formation, supporting that reduced cathode erosion and the system’s long operational lifetime can be expected. The designed ASCENT-propelled PPT can be utilized as an electric propulsion mode in a dual-mode propulsion system combining chemical and electric propulsion modes.